PERTIMBANGAN TERAPI KORTIKOSTEROID PADA STOMATITIS HERPETIK REKUREN - Fitria Mailiza; Riani Setiadhi (B-Dent: Jurnal Kedokteran Gigi Universitas Baiturrahmah, 2015)
Corticosteroid is a group of drugs used as anti-inflamatory and immunosuppresive. Most of the disease which treated with steroids have inflammatory characteristics.This paper is about the management of a 25 year old woman who complained of multiple oral ulcers since 2 months before. Patient had difficulty in eating, drinking and speaking. Before referred to RSUP DrHasan Sadikin she was treated at Hospital X and only got a slight improvement. Diagnosis oral infection Herpes Simplex virus type 1 was made based on anamnesis, clinical examination and laboratory examination (IgG anti HSV-1). Oral lesions showed significant improvement after administration of comprehensive treatment including communication, information and education about the disease as well as topical corticosteroid drug and multivitamin.Corticosteroid was used to limit the inflamatory process caused by the action of T-lymphocytes. However, this drug have many side effects so that practitioners need to consider carefully to use it.Corticosteroid could be considered in the management of oral infections herpes virus type 1 (HSV-1) and showed efficacy in the treatment of this patient.